Non-linear effects of fiscal adjustments on output growth: Does uncertain environment matter? - Soon, Siew Voon (2019)
This paper proposes a Markov-switching model to assess the fiscal adjustments for the period 1990Q1-2018Q3. Our results indicate that the output growth response asymmetry to the change in the budget position only during stable regime. The positive change in the budget position dampens the output growth. It switches from negative effect to positive effect when there is an improvement in the budget position. The role of the fiscal adjustment only a short-run phenomenon and state dependence. However, the uncertainty in the country found temporary increase the output growth, but it is a threat to the country in the long-term.